2016
DOI: 10.1214/15-aos1399
|View full text |Cite
|
Sign up to set email alerts
|

Optimal designs for comparing curves

Abstract: We consider the optimal design problem for a comparison of two regression curves, which is used to establish the similarity between the dose response relationships of two groups. An optimal pair of designs minimizes the width of the confidence band for the difference between the two regression functions. Optimal design theory (equivalence theorems, efficiency bounds) is developed for this non standard design problem and for some commonly used dose response models optimal designs are found explicitly. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In particular, we consider the two regression curves 1,10], and study separately the cases of a Brownian motion and an exponential covariance kernel of the form K(t, t ) = exp{−λ|t − t |} for both error processes ε 1 (t) and ε 2 (t). Following Dette and Schorning (2015), here we focus on the µ ∞ -optimality criterion defined in (2.4) since, as they point out, it is probably of most practical interest and unlike the µ p -criteria for p < ∞, it is not necessarily differentiable. Throughout this section, we denote byθ * n = (θ * 1,n 1 ,θ * 2,n 2 ) the best pair of linear unbiased estimators defined by (4.1), where for each of the combinations of models (5.1) and (5.2) the optimal (vector-) weights have been found by Theorem 4.1 and the optimal design points t * i,j are determined minimising the criterion (4.9).…”
Section: Covariance Kernelmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, we consider the two regression curves 1,10], and study separately the cases of a Brownian motion and an exponential covariance kernel of the form K(t, t ) = exp{−λ|t − t |} for both error processes ε 1 (t) and ε 2 (t). Following Dette and Schorning (2015), here we focus on the µ ∞ -optimality criterion defined in (2.4) since, as they point out, it is probably of most practical interest and unlike the µ p -criteria for p < ∞, it is not necessarily differentiable. Throughout this section, we denote byθ * n = (θ * 1,n 1 ,θ * 2,n 2 ) the best pair of linear unbiased estimators defined by (4.1), where for each of the combinations of models (5.1) and (5.2) the optimal (vector-) weights have been found by Theorem 4.1 and the optimal design points t * i,j are determined minimising the criterion (4.9).…”
Section: Covariance Kernelmentioning
confidence: 99%
“…On the other hand, the efficient planning of experiments for comparing curves has not been dealt with in the literature although this would substantially improve the accuracy of the conclusions drawn regarding non-superiority or equivalence. To the best of the authors knowledge only Dette and Schorning (2015) investigate such a design problem. They consider regression models with independent observations and search for designs that minimise the width of the simultaneous confidence band proposed by Gsteiger, Bretz and Liu (2011), for the difference of the two models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal design problem focusing on the width of the simultaneous confidence bands can be formalized in a different way. When comparing two estimated regression curves, Dette and Schorning (2016) and Dette, et al (2017) proposed to minimize the L por L ∞ -norm of the variance function of the estimator of the difference between the two curves. They demonstrated that their proposal reduces the width substantially compared with the pair of optimized designs for individual regression models.…”
Section: Introductionmentioning
confidence: 99%